Ripper : A Novel - Allende, Isabel; Bock, Oliver (Translator); Wynne, Frank (New York : Harper, 2014)
"A fast-paced mystery involving a brilliant teenage sleuth who must unmask a serial killer in San Francisco through Ripper, the online mystery game she plays with her beloved grandfather and friends around the world"--
Booklist
Publishers Weekly
Kirkus Reviews
Library Journal
Adult.
Adult.
Keywords: Teenagers -- Fiction; Serial killers -- Fiction -- San Francisco (Calif.); Internet games -- Fiction; Mystery fiction; Adventure fiction